Sociology of Family Violence- Notes for First Session - Greenwood, Nancy (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Objectives:A. What is the sociological perspective and what does if offer the study of family violence? B. Why is the study of family violence important to society? C. What is family violence? D. What do the terms conflict, aggression, violence and abuse have in common? E. What are some of the key topics in the sociological study of family violence?